Examination of the impact of sowing technology models on the ear, constiuent and yield parameters of the yield formation elements of maize hybrids of different genotypes - Bene, Enikő (Acta Agraria Debreceniensis, 2013)
Production year 2012 has been characterised by climatic extremities. The weather of this year can be considered very contradictory in terms of maize production. The droughty conditions of the winter and spring months had a negative effect on both germination and starting vigour. The favourable weather of May-July created ideal conditions for intensive growth and generative processes; however the lack of precipitation in August and September had a damaging effect on the development of yield composing elements and grain saturation processes as well. Under such circumstances, the sowing date models caused significant differences in the yield and quality of the hybrids belonging to different growth periods. The growing period of the maize hybrids has been shortened as a result of the unfavourable climatic conditions. Based on the trial results, it is verifiable that short growing period hybrids can be securely sown in draughty years even with a later sowing date, however using a later sowing date in the case of longer growth period hybrids may result even in a yield loss of 2–3 t ha-1. In the case of early and average sowing dates, with given yearly conditions the hybrids of the observed FAO 370-390 hybrid group provided the best result (12.40 t ha-1, 10.99 t ha-1), while in the case of the third, late sowing date the yield dominance of the FAO 290-350 hybrid group is the most significant (10.08 t ha-1). The analysis of the yield composing elements found that the P9578 hybrid has the highest shelling ratio, while its cob is the shortest. The P9494 hybrid has a high yield and the highest thousand grain weight, while the DKC 4983 has the longest cob and its thousand grain weight is above 300 g. The results confirm the fact that DKC 4590 has the highest yield potential and starch content, while in terms of oil and protein content the Szegedi 386 and NK Octet hybrids are the most important.